Korelasi Kadar C-Reactive Protein dan Kualitas Hidup Pasien Hemodialisis Rutin - Ridha Paramadina Aizhar; Mohammad Rudiansyah; Dewi Indah Noviana Pratiwi; Nani Zaitun; FX. Hendriyono (Homeostasis, 2022)
Abstract: HD, or hemodialysis, is a type of kidney replacement therapy that can help patients with RBK live longer and is linked to the continuous inflammatory process. The cognitive and emotional stress connected with HD therapy can have a long-term impact on a patient's quality of life. Acute mass proteins are biomarkers of inflammation caused by C-reactive protein (CRP).. The Short Form-36 is an instrument capable of measuring QoL. The concordance between survival rates and CRP levels in patients having normal hemodialysis was investigated in this study. A total of 74 samples were chosen utilizing a retrospective cross-sectional sampling strategy in this observational analytical analysis. The average CRP was 3.30 mg/L (minimum = 0.20 mg/l; maximum = 36.10 mg/l), according to the findings. The overall mean quality of life score for the participants was 77.28 (minimum = 45.15, maximum = 100.00). In HD patients, there was no significant relationship between CRP levels and quality of life (p=0.319, r=0.117). Keywords: CRP, QoL, short form-36, hemodialysis, chronic kidney disease Abstrak: Satu dari metode pengganti peran ginjal yang mampu memperpanjang usia pasien PGK dan berkaitan erat dengan proses inflamasi yang menetap adalah HD atau hemodialisis. Dalam jangka waktu panjang derajat hidup penderita dapat dipengaruhi oleh tekanan psikis maupun fisik akibat terapi HD. Tanda biologis inflamasi dapat dilihat melalui C-Reactive Protein (CRP) sebagai sebuah protein masa akut. Short Form-36 merupakan instrumen yang mampu mengukur derajat hidup. Korespondensi antara derajat hidup pasien yang rutin melakukan hemodialisis dengan tingkat CRP akan diketahui di penelitian ini. 74 total sampel dipilih melalui teknik random sampling dengan metode retospective cross-sectional pada penelitian observatif analitik ini. Didapatkan hasil studi yaitu nilai median kadar CRP adalah 3,30 mg/L (min = 0,20 mg/L, maks = 36,10 mg/L). Nilai median total skor kualitas hidup subjek adalah 77,28 (min = 45,15, maks = 100,00). Tidak terdapat korelasi bermaknaantara kadar CRP dan kualitas hidup pasien HD (p = 0,319, r = 0,117). Kata-kata kunci: CRP, kualitas hidup, short form-36, hemodialisis, penyakit ginjal kronik.